(untitled) (Journal of Renal and Hepatic Disorders, 2023)
The elderly population is affected by a wide range of kidney diseases like young adult patients. However, their clinical course and morphological manifestations are affected by aging. Recognition, diagnosis, and management of glomerular disease in elderly persons have several unique challenges. We aimed to study the clinicopathologic spectrum of elderly patients with nephrotic syndrome (NS). In this retrospective study, we looked at 234 patients of adult NS who were biopsied during the last 5 years. Among them, 31 patients were above the age of 60 years (Elderly). Mean age in elderly patients was 67.48 ± 6.11 years, with age range from 60 to 86 years. Elderly NS patients constituted 13.2% of total adult NS patients. Nineteen patients (61.2%) were males and 12 (38.7%) were females. Hematuria was observed in 19% and hypertension in 48% patients. Mean serum albumin was 2.79 ± 0.39 g/dl and mean 24 h urinary protein was 3.77 ± 0.8 grams. Membranous nephropathy (MN) followed by minimal change disease (MCD) was the most common diagnosis. No major complication with biopsy was reported in our study as has been the case with most studies.